Intervensi Komunitas Pencegahan Kekerasan Seksual pada Siswi Kelas 11-3 di SMA Al-Muttaqin Kota Tasikmalaya - Fajar Permana; Ismi Tasya Anisa; Vina Sabrina; Ruli Mulya Pratama; Nazwa Rahmadina G; Zilfa Auliyaa Faidah; M Fathan Mubina Ts; Januar Nus Ismail Nugraha; Kharisma Nurul Fazrianti Rusman (Lembaga Pengembangan Kinerja Dosen, 2025)
Sexual violence is a serious problem that has long-term impacts, especially for teenagers. This community service activity aims to increase high school students knowledge and awareness of sexual violence thorugh interactive counseling, educational videos, and group discussions. The results showed an increase in understanding, courage to voice opinions, and participants’ awareness of the risk of violence, Community education has provento be effective as a strategy to prevent sexual violence in teenagers.